Differences in UGT1A1 gene mutations and pathological liver changes between Chinese patients with Gilbert syndrome and Crigler-Najjar syndrome type II. Issue 45 (November 2017) - Sun, Lei; Li, Man; Zhang, Liang; Teng, Xiaoying; Chen, Xiangmei; Zhou, Xingang; Ma, Zhiyuan; Qi, Liming; Wang, Peng
Abstract : Abstract: Diagnosis of Crigler-Najjar syndrome type II (CNS-II) and Gilbert syndrome (GS) based on the serum bilirubin concentration is difficult, because this parameter can fluctuate under certain conditions. The aim of this study was to explore differences in UGT1A1 gene mutations, which cause both CNS and GS, and pathological changes between CNS-II and GS. Ninety-five Chinese patients with hereditary unconjugated hyperbilirubinemia were enrolled in this study. Peripheral blood samples obtained from patients were used to evaluate bilirubin levels and for UGT1A1 gene testing. Percutaneous needle biopsy of the liver and staining of tissue samples with hematoxylin and eosin, Masson trichrome, reticulin, and Perl Prussian blue were performed for 59 patients. The Ishak scoring system was used to assess inflammatory activity and the extent of fibrosis. One hundred ninety-two UGT1A1 mutations at 6 sites were detected in the 95 patients; the most common mutation in GS was c.-3279T>G in the phenobarbital response enhancing motif of the UGT1A1 promoter, whereas the most common mutation in CNS-II was p.G71R. The frequency of heterozygous p.G71R mutations in CNS-II was significantly higher than that in GS ( P  = .001); however, the frequency of homozygous c.-3279T>G mutations in CNS-II was markedly lower than that in GS ( P  = .032). Among all patients with multiple mutations, the frequency of p.Y486D was significantly higher in CNS-II than in GS ( P  = .007). The frequency of compound c.-3279T>G, A(TA)7 TAA, and p.G71R mutations in CNS-II was significantly higher than that in GS ( P  = .001). Among the 59 patients who underwent percutaneous needle biopsy, 20 had iron deposition in the liver. The frequency of hepatic iron deposition in CNS-II was significantly higher than that in GS ( P  = .002). The linked polymorphic mutations, A(TA)7 TAA and c.-3279T>G in UGT1A1, were most strongly associated with GS, whereas mutations in the coding region, especially p.G71R and p.Y486D, were more strongly associated with CNS-II. Iron deposition was more common in liver biopsies from patients with CNS-II than in those with GS.